Covering It Up? Questions of Safety, Stigmatization, and Fairness in Covert Medication Administration. Issue 2 (June 2017) - Simpson, Christy
This paper examines the practice of covert medication administration from an organizational ethics perspective. This includes consideration of vulnerability and stigmatization, safety, and fairness (justice) in terms of the culture of health care organizations and the relevance of policies and processes in relation to covert medication administration. As much of the discussion about covert medication administration focuses on patients and health care providers, this analysis aims to help expand the analysis of this practice.